Rural and Urban Disparities in Caries Prevalence in Children with Unmet Dental Needs: The New England Children’s Amalgam Trial - Nancy Nairi Maserejian, ScD; Mary A. Tavares, DMD, MPH; Catherine Hayes, DMD, SM, DrMedSc; (Blackwell Synergy, 2008)
To compare the prevalence of caries between rural and urban children with unmet dental health needs who participated in the New England Children’s Amalgam Trial.